Efficacy of a Student-Run Ophthalmology Service in Managing Diabetic Retinopathy: A Five-Year Retrospective Review - Jody He; John Goté; Haley D'Souza; Daniel Barmas-Alamdari; Giovanni DiSandro (Journal of Student-Run Clinics, 2022)
Background:Diabetic retinopathy is one of the leading causes of blindness in the world, and its development and progression can be prevented with appropriate glycemic control. The Health Outreach Partnership of EVMS Students (HOPES) Student-Run Free Clinic at Eastern Virginia Medical School (Norfolk, VA) provides both primary care and ophthalmology care to patients from underserved backgrounds. The purpose of this retrospective chart review is to assess whether a student-run free clinic’s primary care and ophthalmology services are effective in preventing the development and progression of diabetic retinopathy.Methods:Inclusion criteria were a diagnosis of Type 2 Diabetes Mellitus (T2DM), two or more HOPES Ophthalmology Clinic appointments separated by at least 4 months between January 2015 and July 2019, and medical management of T2DM by the HOPES Primary Care Clinic. Objective patient data collected were HbA1c, visual acuity, and documented dilated fundus examination findings.Results:There were 174 HOPES Ophthalmology visits and 66 diabetic eye exam appointments in this five-year time period. The average HbA1c for patients at the initial appointment with the Ophthalmology Clinic was 7.77% ± 1.65% and the average HbA1c at the most recent appointment was 7.4% ± 2.28%. Among all patients, there was no statistically significant change in visual acuity in either eye from baseline to the most recent visit. There was no change in fundus examination findings in any of the patients from their initial visit to their most recent visit.Conclusions:The HOPES Clinic has been effective in preventing the development and progression of diabetic retinopathy in its patients who regularly follow up with both the primary care and ophthalmology clinics. This study highlights that a student-run free clinic is capable of making an impact in the community by preventing the development of a potentially blinding disease, but that further strategies to enable consistent patient follow-up are needed.